Análise das competências digitais dos professores da Universidade Federal do Yocantins – câmpus Palmas - Carvalho, Yasmin Barbosa de (Universidade Federal do Tocantins, 2021)
This work aims to analyze or the level of proficiency in digital technologies of UFT professors, Câmpus Palmas, based on the DigCompEdu “Check-In” self-assessment model. Model developed by the European Union Science Center. More punctually, this research includes the digital skills of documents in three specific dimensions, which are: professional, pedagogical and student. An assessment of the level of digital proficiency, seeks to measure an individual's competence in the Digital Information and Communication Technologies (TDIC) treaty for beneficiaries themselves and third parties. This assessment of digital skills measured by scales, used as a methodological procedure of quantitative approach of an exploratory and descriptive nature. Gil (2008) was used to understand a content analysis and an association of statistical methods on a collected sample.This research was carried out with 102 professors from the Campus Palmas, distributed in the most diverse areas of knowledge. In the theoretical framework, policies to promote TDIC in the educational environment, Brazilian education policies, research at international, national, state and municipal levels on the same theme were addressed. The largest audience of the survey is female, the largest age group of participants is between 40 and 49 years. Through data analysis, this research shows that, in general, the professors of UFT, Câmpus Palmas are classified in the Integrator Profile, level B1, that is, they have a moderate level of digital proficiency. Statistically, the average global performance regarding the variables sex, age, area of education or education, did not have significant differences in terms of the range of competences